Tailor system using earliest due date scheduling technique / Suhailah Othman - Suhailah, Othman (2017)
Tailor System Using Earliest Due Date Scheduling Technique is about producing schedule to align the customer booking that include the time for and promise date from tailor for each customer. First of all, before producing this schedule, some data need to capture and analyzes like processing time for each cloth, due date from customer, last date in schedule, measurement cloth of customer and also customer detail. This data need to be keep and calculate it. This title come up in view of issue that occur at Saadiah tailor shop which tailor hard to manage what cloth need to do first, what cloth can be delay based on deliverable date. Other than that, the business also had some issue like customer do not know status of their cloth and tailor not alert with the deliverable date. This issue will give big impact to their business and also the customer satisfaction. From that situation, this project come up with schedule using Earliest Due Date Scheduling Technique. The methodology for this project is system development planning which contains five phase which are planning, gathering requirement, analyse, design and lastly implementation phase. Based on that, the phase need to be complete from one phase to another phase align with the deliverable for each phase. Planning phase will provide schedule plan for this project, second and third phase will obtain clear requirement from stakeholder, fourth phase will inherited document from third phase which is software requirement specification and lastly is development of tailor system into real system. The development of this system have some limitation which is this system is not like application that can be download in mobile phone. It only compatible in computer or laptop to use it. Based on that, for the future work, this system can be improve by using a mobile application for ease of user.